PENGARUH LITERASI PERPAJAKAN DAN EFEKTIVITAS PENGELOLAAN KEUANGAN TERHADAP KEWAJIBAN PERPAJAKAN UMKM DI KOTA TANGERANG SELATAN - Irma Anggraeni; Titah Rahmawati (Journal of Research and Publication Innovation, 2026)
This study examines the influence of tax literacy and financial management effectiveness on the tax obligations of Micro, Small, and Medium Enterprises (MSMEs) in South Tangerang City. The low level of tax compliance among MSMEs, despite the implementation of a 0,5% final income tax rate under Goverment Regulation No. 23 of 2018, indicates a gap between potential and actual tax revenue. Using a quantitative approach, data were collected through questionnaires distributed to 105 MSME actors selected by accidental sampling. The data were analyzed using multiple linear regression preceded by validity, reliability, and classical assumption tests.